1991
DOI: 10.2307/1591619
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Avian Infectious Bronchitis Virus by Cold-Adaptation

Abstract: Avian infectious bronchitis virus (IBV) Arkansas-type DPI strain was passaged 10 times in specific-pathogen-free (SPF) chicken embryos incubated at 28 C and 37 C. Virus grown at 28 C acquired cold-adapted (CA) and temperature-sensitive (TS) characteristics based on more-rapid growth at 28 C and a reduced ability to grown at 41 C, respectively, compared with non-cold-adapted (non-CA) virus grown at 37 C. The pathogenicity and immunogenicity were determined for CA and non-CA IBV in 1-day-old SPF chickens followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…IBV has been isolated from the Harderian gland (Dhinakar Raj & Jones, 1996a;Gelb et al, 1991b;Toro et al, 1996a) and IBV-positive cells have been shown in the stroma of the gland by IF staining (Toro et al, 1996a). IBV vaccination by eyedrop resulted in a massive infiltration of lymphocytes, increase in plasma cell numbers (Davelaar & Kouwenhoven, 1976;Survashe et al, 1979;Montgomery et al, 1994;Toro et al, 1996a) and desquamation of tubular epithelium in the Harderian gland with restoration from 14 days after vaccination (Toro et al, 1996a).…”
Section: Virus In Other Tissuesmentioning
confidence: 99%
“…IBV has been isolated from the Harderian gland (Dhinakar Raj & Jones, 1996a;Gelb et al, 1991b;Toro et al, 1996a) and IBV-positive cells have been shown in the stroma of the gland by IF staining (Toro et al, 1996a). IBV vaccination by eyedrop resulted in a massive infiltration of lymphocytes, increase in plasma cell numbers (Davelaar & Kouwenhoven, 1976;Survashe et al, 1979;Montgomery et al, 1994;Toro et al, 1996a) and desquamation of tubular epithelium in the Harderian gland with restoration from 14 days after vaccination (Toro et al, 1996a).…”
Section: Virus In Other Tissuesmentioning
confidence: 99%
“…Concurrent circulation of both classic and variant IBVs have been identified in most parts of the world, raising major challenges to global prevention and control efforts. During the past few decades, there have been reports of new virulent field isolates that represent variant strains, which can cause wide tissue tropism and high pathogenicity (Gelb et al, 1991;Jackwood, 2012;Shaw et al, 1996;Zanella et al, 2000). Though the mechanisms behind chickens' varying susceptibility to different IBV infections have been studied, little to no data is available on comparative immunopathogenesis on recently emerged IBVs.…”
Section: Introductionmentioning
confidence: 99%
“…Current IBV isolates present high antigenic diversity (Hofstad, 1975), and emergent strains that differ in antigenic properties, tissue tropism and pathogenicity are continuously being reported across the world (Gelb et al, 1991;Jackwood, 2012;Shaw et al, 1996;Zanella et al, 2000). While all IBV strains appear to initially infect chickens via the respiratory tract, vireamia enables spread to secondary sites for further replication and persistence.…”
Section: Introductionmentioning
confidence: 99%